Instructional Leadership in Malaysia - Hassan, Roslizam; Ahmad, Jamilah; Boon, Yusof (International Journal of Engineering and Technology, 2018)
Leadership of school leaders regardless principals or headmasters is among the key factors that can affect the academic achievement of students directly or indirectly. Based on previous research, a strong relationship between student achievement and leadership of school leaders was proven. The Ministry of Education Malaysia (MoE) has outlined three approaches to improving student achievement through the improvement of school leaders' performance. One of the approaches is school leaders should act as instructional leaders who are actively involved in teacher development activities by planning, coordinating and evaluating the teaching and learning process (T&L) at school. This concept paper will discuss several matters related to instructional leadership such as background and development of instructional leadership, instructional leadership definitions, the development of instructional leadership concepts, instructional leadership models and the issues and challenges that exist in implementing this leadership styles. The analysis was done in the context of Malaysia and abroad. The paper is written based on extensive secondary data analysis. After analyzing matters relating to instructional leadership, it can be concluded that instructional leadership is a form of leadership that every school leader needs to practice for excellence achievements in a school. With a lot of challenges nowadays, it needs to be addressed so that the direction of the school is on the right track and studentsâ€™ achievement can be enhanced.Â